Image translation of Bangla and English sign language to written language using convolutional neural network - Bismoy, Muttaki Islam; Shahrear, Fahim; Mitra, Anirban; Bikash, D M; Afrin, Ferdousi (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.